Pengaruh Word Of Mouth Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Ark Interior & Exterior Di Ponorogo - Winarno, Moh Abu Ali; Khalikussabir, Khalikussabir; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze and describe the influence of word of mouth and service quality on customer satisfaction at ARK Interior & Exterior in Ponorogo Regency. The population in this study consists of customers who have used the services of ARK Interior & Exterior. The sample size was determined using the Malhotra formula, resulting in a total of 50 respondents. Data collection was carried out using questionnaires. To address the research problems, SPSS was employed, and the analytical methods used in this study include validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, F-tests, t-tests, and determination coefficient tests (R²). The results of the study indicate that word of mouth has a significant effect on customer satisfaction, while service quality does not have a significant effect on customer satisfaction. Keywords: Word of Mouth, Customer Satisfaction, and Service Quality